GAMBARAN KARAKTERISTIK WANITA YANG MENGALAMI KANKER SERVIKS DI RUMAH SAKIT UMUM DAERAH (RSUD) PANEMBAHAN SENOPATI BANTUL YOGYAKARTA - Fatimah Dewi Anggraeni; Retno Rahayu (MEDIA ILMU KESEHATAN, 2017)
Background : Cervical cancer is still becoming the most prevalent diseases in Indonesia. Health Department of Indonesia in 2012 recorded that the predicted incidence and mortality rate which caused by cervical cancer were 13.2 million of lifes. Factors that affecting cervical cancer are age, education, job, parity, and hormonal contracepcy. This statement is supported by the Hospital Information System (HIS) data in the year of 2013 which showed that there were 130 cases of cervical cancer in Yogyakarta (DIY). The opreliminary study obtained that in 2015 there were 50 persons of cervical cancer sufferer in Panembahan Senopati Public Hospital, which were consist of 40 outpatient cases and 10 inpatient cases. Aim : This study aimed to know the characteristics of mothers who encounter cervical cancer. Research Methods : This research was a descriptive quantitative research. The sampling technique used in this research was total sampling technique. The samples were 50 respondents with frequency distribution that obtained by using secondary data and checklist methods. Results : Most of mothers who encounter cervical cancer in Panembahan Senopati public hospital Bantul Yogyakarta that aged >35 years old were as many as 34 respondents (68.0%), as many as 26 respondents (52.0%) were high school educated or graduated, as many as 18 repondents (36.05) were statused as a farmer, as many as 18 repondents (36.0%) were primiparas and grandemulti parity, and as many as 29 respondents (58.0%) were using hormonal contracepcy. Conclusion : Mothers who encounter cervical cancer in Panembahan Senopati public hospital Bantul Yogyakarta that aged >35 years old were: high school educated or graduated, farmers, primiparas and grandmultiparas, and using hormonal contracepcy. Keywords : Characteristic, Cervical cancer.